Psikologi Keluarga Sebagai Pedoman dalam Pola Pengasuhan Anak Remaja - Fatiha Sabila Putri Matondang; Mukhlis Tri Mulya Marpaung; Muhammad Alfath Lubis; Juli Aini Syafitri Lubis; Rahma Aulia (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
The personality of a child is heavily influenced by genetic and environmental factors, the urgency of the role of the parent in the formation of the child's personality is of paramount importance, since the parent is the first to make a contribution to a child' s personality. Parental patterns are crucial to children's development. In addition, adolescence is a transition from childhood to adulthood, where changes occur, including physical, social, and mental changes. With all these changes, adolescents face the challenge of controlling their emotions and behaving according to social norms. Parental patterns also play a role in the process of changes that adolescents experience, as well as how they behave and behave in society. The aim of this study was to find out how parental patterns relate to the development of children in adolescence.